The role of cultural capital on the voluntary contributions to cultural goods: A differential game approach - Massimo Finocchiaro Castro; Isidoro Mazza; Domenica Romeo (Games, 2021)
This study aims to offer a formal analysis which relates provision of cultural goods to the society's level of cultural capital. Such a level is assumed to already exist in society and is increasable thanks to individual support for the offer of cultural goods. The achievement of the highest levels of cultural capital increases satisfaction coming from cultural goods consumption, and then voluntary contributions. Social approval, deriving from donations, is positively related to society's existing cultural capital and triggers a positive externality for donators, thus increasing contributions and generating a positive externality for the whole society. The dynamic analysis provided in this study requires the adoption of a differential game where individuals interact, making their choices on their voluntary contribution level. We find that, under certain conditions, the solution obtained for the Nash equilibrium with closed-loop strategies provides optimal level of cultural capital that exceed the Pareto efficient solution obtained through open-loop strategies.
Keywords: 330; cultural capital; differential games; public goods; social approval; voluntary offer